Parenting Patterns and Digital Media: A Case Study of the Socialization Process and Character Formation of Children in Kindergarten - Nurfadia Reski Azizan; Hajerah Hajerah; Fatimah Azzahrah; Naila Farila; Nur Sahrah Sarkia (Ihya Ulum: Early Childhood Education Journal, 2026)
In the era of rapid digital transformation, digital media has permeated Indonesian family life, often functioning as a "digital babysitter" that disrupts early childhood socialization and character formation. This study analyzes how digital parenting patterns influence the socialization process and character development of children at Generasi Tanpa Batas Kindergarten, Takalar Regency. Employing a descriptive qualitative approach with a single case study design, data were collected over five days through participatory classroom observations, in-depth interviews with the principal, a classroom teacher, and four purposively selected parents, alongside documentation. Data were analyzed using an interactive model encompassing reduction, display, and conclusion drawing. The findings reveal three dominant digital parenting patterns with distinct developmental outcomes. First, permissive-digital parenting, characterized by excessive screen time, results in low frustration tolerance, verbal aggressiveness, and limited expressive vocabulary. Second, authoritarian-digital parenting, which imposes a total gadget ban, paradoxically triggers obsessive interest and hidden gadget use among children. Third, authoritative-digital parenting, involving limited screen time and active co-viewing, fosters optimal socialization, empathy, verbal conflict resolution, and an adaptive reflective habitus. The study concludes that without active parental mediation, digital media risks replacing crucial humane interactions necessary for primary socialization. Therefore, a structured, collaborative digital-literacy approach between families and early childhood education institutions is urgently needed to optimize children's socio-emotional development and character building in the digital age.